(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Ukraine is a country with immense potential for entrepreneurship, but it faces significant challenges that can hinder the growth of its entrepreneurial ecosystem. This article explores the challenges that Ukrainian entrepreneurs face and how they can be overcome, as well as the role of government and other organizations in supporting entrepreneurship. One of the biggest challenges for Ukrainian entrepreneurs is access to funding. Ukraine has a developing financial market, and it can be difficult for entrepreneurs to secure loans or investments. This is com-pounded by the lack of a well-developed venture capital market, which makes it difficult for entrepreneurs to access the capital they need to grow their businesses. The article uses quantitative methods of research, modeling the influence of factors on the efficiency of the ecosystem